An Overview on Intranasal Drug Delivery System: Recent Technique and Its Contribution in Therapeutic Management - Anu; S K Gupta; Shobhit Kumar (Current Research in Pharmaceutical Sciences, 2019)
Nasal drug administration has been used as an important another route for the systemic availability of drugs. Intranasal route has large surface area, high total blood flow, avoidance of first-pass metabolism, porous endothelial membrane, and ready accessibility. For nasal route administration various drugs including peptide and protein drugs, for systemic medication has been widely used in recent few years. This review article highlights the importance, strategies and advantages of the nasal drug delivery systems. Various methods are discussed here for increasing the residence time of drug formulations in the nasal cavity, for improving nasal drug absorption. In this review article we discuss the effects of bioadhesive drug delivery systems on nasal drug administration. Drug delivery systems (such as nanoemulsion, microspheres, liposome and gels) have good bioadhesive characteristics which swell easily when in contact with the nasal mucosa. These types of drug delivery systems protect the drug from enzymatic degradation in nasal secretions and also control the rate of drug clearance from the nasal cavity.